Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) - linda novita dewi; Dicky Jhoansyah; Kokom Komariah (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
The purpose of this study was to determine whether there was an increase or not on the financial performance of the property, real estate and building construction sector which conducted in IPO 2017 on the Indonesia stock exchange. The research method used in this study is a quantitative research method with a descriptive analysis approach. The sampling technique used was purposive sampling technique with predetermined criteria. Of the 6 issuers conducting IPOs in 2017, there were 4 companies selected as research samples. Data collection techniques in this research is the study of literature and documentation. Data analysis techniques used in this study are horizontal analysis with liquidity ratios, activities, solvency and profitability using the CR, cash ratio, TATO, DER, LTDtER, ROA, and ROE models. The result of this study indicate an increase and decrease in financial performance after the IPO in each sample if measured using CR, cash ratio, TATO, DER LTDtER, ROA and ROE.